Investigation the properties of sustainable ultra-high-performance basalt fibre self-compacting concrete incorporating nano agricultural waste under normal and elevated temperatures - Sahar A. Mostafa; Bassam A. Tayeh; Ibrahim Almeshal (Case Studies in Construction Materials, 2022)
Producing sustainable concrete using waste materials has a noticeable impact on the environment. From another aspect, understanding the effect of high temperature on concrete can help in reduce the environmental fire impact and lower rehabilitation costs. This study presents a systematic experimental investigation to produce sustainable ultra-high-performance basalt fibre self-compacting concrete (UHPBF-SCC) using agricultural waste materials including nano sugar cane bagasse, nano cotton stalk ash and nano rice straw ash as cement replacement. The three dosages of nanoparticles are mechanically produced after heat treatment at 700°C. The performance of the three dosages of nanoparticles (partially replacing 1–5% of cement) was investigated in the presence of basalt fibre. This study also examines the effect of elevated temperatures of 300°C and 600°C on the behaviour of UHPBF-SCC. The physical properties, including passing ability, flowability and segregation resistance, were studied. Compressive strength, strength loss at elevated temperature, mass loss, ultrasonic pulse velocity, splitting, and flexure strength were also investigated. Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDX) analysis were conducted to show the microstructure of the mixes. Mechanical characteristics are significantly increased in the presence of nanoparticles, more than 18% in compressive, 32% in tensile strength and 28% in flexure strength compared with the reference mix. SEM analysis showed compacted sections with high bonded matrix and high ITZ at normal conditions, but microcrack propagation appeared at 300°C and 600°C due to ettringite decomposition and evaporation of capillary and adsorbed water. EDX analysis showed high Ca/Si with the addition of nanomaterials.